1998
DOI: 10.1007/bf02962364
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, placebo-controlled trial of the immune modulator WF10 in patients with advanced AIDS

Abstract: A randomized, double-blind trial compared treatment with the immune modulator WF10 (ten patients) and placebo (nine patients) administered in cycles over 3 months among individuals with advanced AIDS. There were no notable clinical adverse events; changes in hematologic and chemistry values were comparable in the two groups. In both groups, median HIV-RNA PCR values remained stable. Immunologic variables showed a consistent tendency to increase in the WF10 group and to decrease in the control group, with signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
2
8
0
3
Order By: Relevance
“…During the past 30 years in vitro analyses, animal studies and clinical trials have shown that preparations of pharmaceutical NaClO 2 not only exerted antiviral and antimicrobial effects [31]–[34], but also promoted tissue regeneration and wound healing following radiation, chemotherapeutic, ischemic, metabolic, or infectious injuries [35][39]. Although the oxidative processes and molecular mechanisms underlying these findings have not yet been defined in detail, pharmaceutical NaClO 2 clearly promotes cell proliferation, hematopoiesis, and microcirculatory blood and oxygen supply, modulates the functions of immune cells, and limits inflammatory responses [40][44].…”
Section: Introductionmentioning
confidence: 99%
“…During the past 30 years in vitro analyses, animal studies and clinical trials have shown that preparations of pharmaceutical NaClO 2 not only exerted antiviral and antimicrobial effects [31]–[34], but also promoted tissue regeneration and wound healing following radiation, chemotherapeutic, ischemic, metabolic, or infectious injuries [35][39]. Although the oxidative processes and molecular mechanisms underlying these findings have not yet been defined in detail, pharmaceutical NaClO 2 clearly promotes cell proliferation, hematopoiesis, and microcirculatory blood and oxygen supply, modulates the functions of immune cells, and limits inflammatory responses [40][44].…”
Section: Introductionmentioning
confidence: 99%
“…WF10 has been approved in Thailand for systemic administration to patients with postradiation syndrome and for supportive care in patients being treated for cancer. These indications have been studied extensively and reviewed [2]. Oxoferrin is used topically to enhance healing of chronic wounds such as diabetic ulcers [3].…”
mentioning
confidence: 99%
“…Among the therapeutic approaches against inflammatory diseases is the intravenous infusion of the chlorite-based immunomodulatory drug solution WF10. This drug solution and the more diluted form Oxoferin have been successfully applied to dampen strong inflammatory states and to improve wound healing processes in patients [10][11][12][13]. However, the fine mechanism of the action of WF10 remains unknown.…”
Section: Introductionmentioning
confidence: 99%